Clinical and hardware evaluation of moisturizing properties and tolerability of a emollient cream with filagrinol ("Admera") in atopic dermatitis in children - S. S. Masalskiy; Yu. S. Smolkin; O. Yu. Smolkina (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Objective. Evaluate the possibility of using a cream with 5 % filagrinol ("Admera") in children (0-18 years old) as an emollient in atopic dermatitis (AtD) and receive hardware measurements of skin hydration.Materials and methods. Open interventional study in parallel groups of children with AtD 0-18 years old (n = 72, median age 6 [3.75; 7.0] years). 2 equal groups: group 1 received methylprednisolone cream 1 time daily on lesions for 14 days + Admera emollient on the other skin; group 2 received the same treatment + cream with filagrinol 5 % applied from day 5 on the lesions.Results. Standard therapy with topical steroids and emollients was effective. The severity indices during steroid + emollient treatment decreased significantly: EASI 11.5 [6.0; 17.0] vs 2 [1; 3.8] scores, p < 0.001; skin lesion area from 17.5 % [10.0; 26.8 %] to 3.5 % [1.25; 6.0 %], p < 0.001; IGA score - 2 [2; 3] vs 1 [1; 2], p < 0.01.The total itching score for AtD (max 10) became significantly lower with therapy: nocturnal itching decreased from 3 [1; 7] to 1 [1; 3] and daytime itching from 4 [3; 7] to 2.5 [1; 4] points, p < 0.01.The mean values of hardware-measured skin hydration outside the lesion areas were 8 [6.0; 12.0] units at baseline. After 14 days of emollient, hydration of dry clear skin increased to 10 [8.0; 15.0] units (p = 0,017). The hydration of the skin on the affected areas increased significantly from 8 [6; 10] to 12.0 [8; 15] units (p = 0.001).The patients' organoleptic evaluation of the cream was 4.48 (max 5). No serious or moderate adverse events (AEs) were reported in this study. In 11.3 % of cases, the skin itching was detected, but resolved rapidly without treatment.Conclusion. The cream with 5 % filagrinol ("Admera") significantly improved skin hydration, as measured instrumentally, in the area of dermatitis and dry skin without ones. The cream caused no significant adverse reactions and could be used together with topical steroids.